Social isolation and cognitive decline among older adults with depressive symptoms: prospective findings from the China Health and Retirement Longitudinal Study. (July 2021) - Guo, Lizhi; Luo, Fengping; Gao, Ningcan; Yu, Bin
Highlights: Identifying potentially modifiable risk factors of cognitive decline among people with depressive symptoms could provide insight into strategies for improving treatment effect of depression and prevention of dementia. Quite a few studies have examined the association between social isolation and cognitive function directly among depressed older adults and the results are still mixed. Social isolation was significantly associated with 4-year memory decline among depressed older women (but not men) in China. Abstract: Objectives: : Identifying potentially modifiable risk factors of cognitive decline among people with depressive symptoms could provide insight into strategies for improving treatment effect of depression and prevention of dementia. Quite a few studies have examined the association between social isolation and cognitive function directly among depressed older adults and the results are still mixed. The aim is to examine the association of social isolation and cognitive decline among older adults with depressive symptoms in a non-Western country. Methods: : This study used data from the China Health and Retirement Longitudinal Study (CHARLS). Depressive symptoms were measured by the Chinese version of the 10-item Center for Epidemiological Studies Depression Scale (CESD-10) (elevated depressive symptom cutoff ≥ 10). Social isolation was assessed based on responses to four items: marital status, residence, contact with children, and social activity. Lagged dependent variable regressions adjusted for confounding factors were used to evaluate the association between baseline social isolation and follow-up cognitive function. Results: : A number of 2, 507 participants [mean age (SD)=61.37 (7.26); male, 41.0%] with increased depressive symptoms were available for the present study. Baseline social isolation was significantly associated with 4-year episodic memory (β=−0.08, p <0.001) in depressed women, but not men (β=−0.03, p =0.350). No significant association between baseline social isolation and follow-up mental status was found for women (β=−0.04, p =0.097) or men (β=0.01, p =0.741). Discussion: : This longitudinal study found that social isolation was significantly associated with memory decline over 4 years among depressed women (but not men) in China.